2013
DOI: 10.3171/2013.1.jns121696
|View full text |Cite
|
Sign up to set email alerts
|

Low triiodothyronine syndrome as a predictor of poor outcomes in patients undergoing brain tumor surgery: a pilot study

Abstract: Object A low triiodothyronine (T3) state is highly prevalent and is associated with a poor prognosis in critically ill patients. The authors investigated, in patients undergoing brain tumor surgery, the direct association of a perioperative low T3 syndrome with clinical outcomes and also with symptoms of depression and anxiety. Methods Ninety consecutive patients (71% women, median age 55 years), on admission for brain tumor surgery, were evaluated for sociodemographic and clinical characteristics. Their thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…These findings agree with previous data showing 8-fold greater risk for poor discharge outcomes in brain tumor patients with reduced free triiodothyronine concentrations [15]. An association of lower triiodothyronine concentrations with worse hospital discharge outcomes was previously reported in stroke [21] aneurysmal SAH [22] patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings agree with previous data showing 8-fold greater risk for poor discharge outcomes in brain tumor patients with reduced free triiodothyronine concentrations [15]. An association of lower triiodothyronine concentrations with worse hospital discharge outcomes was previously reported in stroke [21] aneurysmal SAH [22] patients.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of the Low triiodothyronine syndrome was the highest in high-grade glioma patients. In a previous study of 90 patients with primary and metastatic brain tumors, we found that 38% of patients had reduced triiodothyronine concentrations before surgery, and that the prevalence of the Low triiodothyronine syndrome increased to 54% after surgery [15]. Greater prevalence rate of the Low triiodothyronine syndrome in the present study can be explained by the greater number of patients with malignant gliomas (21% vs. 13%) included in the present cohort.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Moderate-severe depressive symptoms were associated with worse HRQoL across all SF-36 dimensions. Mood symptoms and disorders are common [2527] and were document as independent predictors of worse HRQoL of brain tumor patients [3, 26]. Functional dependence was associated with worse HRQoL in all but mental health domains suggesting that functional status should be considered important for HRQoL of brain tumor patients.…”
Section: Discussionmentioning
confidence: 99%